An Analysis of Glass Fracture Statistics - David T. Kinsella; Kent Persson (Challenging Glass Conference Proceedings, 2018)
A numerical method is applied to model the fracture stress and failure location in glass panes subjected to various bending arrangements. The method assumes the weakest-link principle and the existence of surface microcracks. The fracture stress and failure origin are revealed through a search algorithm. The magnitude of strength and the location of fracture are stochastic in nature and can be predicted based on a suitable representation of the surface flaws condition. When the crack size distribution is assumed to be Pareto, the strength distribution is found to be very similar to a Weibull distribution. The stresses in large laterally supported plates which are subjected to uniform pressure are modelled and the distribution of fracture location is determined based on a single population of cracks with a Pareto distributed crack size. Two types of gasket support materials are considered, neoprene and nylon. The softer gasket material produces a greater number of fractures nearer the corners of the plate. A comparison is made with the recorded fracture locations according to various experiments. In addition, a tall vertical panel of laminated glass with a complex geometry and which is subjected to dynamic impact loading is modelled and the distribution of fracture location is determined based on a single population of cracks with a Pareto distributed crack size.